From heresy to orthodoxy: apocrypha and canonization in Chinese Buddhism – the case of the Consecration Sūtra (Guanding jing guan ding jing) - Zheng, Qijun (Studies in Chinese Religions, 2025)
This article re-examines canon and canonization in Chinese Buddhism through a focused case study of the Consecration Sūtra (Guanding jing guan ding jing, T no. 1331). The opening section treats ‘canon’ and ‘canonization’ as analytic categories rather than emic absolutes. Chinese developments are then situated within debates on open versus closed canons, cataloguing practice and standards of authenticity, showing how an initially flexible corpus moved toward relative closure while remaining contested. The case study traces how authorship, attribution and bibliographic control operated in this text. Its distinctive anomalies – including life‑prolonging rites employing banners and lamps – are shown to cluster in the later strata, especially juan 11–12. Correlating lexical and ritual markers clarify why juan 12 constitutes the earliest securely datable Chinese witness to Bhaiṣajyaguru, attained exceptional circulation, and plausibly informed later recensions, even as Sengyou registered it under the categories of ‘doubtful’ and ‘spurious.’ The analysis further indicates that such apocrypha functioned as engines of sinification, translating doctrine into locally compelling rituals while probing the limits of catalogue authority. The conclusion characterizes Chinese canonization as an ongoing negotiation among institutional gatekeeping, ritual efficacy and lay soteriological demand, and shows that in practice popularity and normative legitimacy frequently diverged.